Rasio Likuiditas, Rasio Solvabilitas Dan Rasio Profitabilitas Terhadap Price To Book Value (PBV) Pada Perusahaan Food And Beverage Tahun 2011-2014 - Aziz, Muhammad Abdul, Dr. Syamsudin, M.M (2016)
The writer do the research to show the significant impact in accordance with partial as well as simultaneous in the variable of current ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) toward Price to Book Value at the Food and Beverage company, or sub sector of food and drink which registered in the Indonesia stock exchange period 2011-2014. Whose research is quantitative by using purposive sampling technique thoughtful determining sample, and it can be able to obtained of 16 companies from 20 companies. The writer used a secondary data based on ICMD (Indonesia Capital Market Directory) in the Indonesia stock exchange. To show the analysis method in this research, the writer used an analysis descriptive, regression double linear, classic assumption testing consider: normality testing, multicolinearity testing, auto-correlation testing, and heteroskedasity. Beside that, this method also exist the hypotheses testing by using T technique. F testing toward significant level of 0,05 and coefficient determination (R2). The result of the study shows that in the classical assumption test is not found any problem. Partially shows that the negative variable of current ratio (CR) and variable of Debt to Equity Ratio (DER) do not influence the Price To Book Value (PBV). Net Profit Margin variable influences the Price To Book Value (PBV). Simultaneously, shows that Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) influences the Price To Book Value (PBV) obtained 4.722 Fhitung with significant value 0,005. With the result of the determination coefficient Rsquer obtained 0,151 which mean 15,1% variabel Price To Book Value (PBV) can be explained by CR, DER, and NPM variable, the 84,9% residue is explained by actors outside the research.